2019
DOI: 10.1016/j.rbmo.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acids and IVF treatment

Abstract: Omega-3 polyunsaturated fatty acids (PUFAs) are essential fatty acids, derived mostly from fish oil, that have a significant anti-inflammatory effect. Data from animal studies support their role in the reproductive mechanism, and recent human studies suggest a positive effect on sperm quality and natural conception. Their general role in human fertility, and specifically in IVF treatment, however, is not clear. A few small, prospective cohort studies have examined the relationship between serum PUFAs and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…Other authors reported a lower seminal n-6/n-3 ratio in fertile men compared to the infertile ones, probably due to a significantly high amount of total n-3 PUFAs [41]. Recent investigation supports this observation where total n-3 PUFAs of normozoospermic individual's semen were significantly higher than those from men with oligozoospermia, asthenozoospermia, and oligoasthenozoospermia [71]. In addition, in normozoospermic subjects, it was shown that about 50%, 30%, and 20% of the total FAs were composed of SFAs, PUFAs, and MUFAs, respectively.…”
Section: Fatty Acids In Human Spermatozoamentioning
confidence: 82%
“…Other authors reported a lower seminal n-6/n-3 ratio in fertile men compared to the infertile ones, probably due to a significantly high amount of total n-3 PUFAs [41]. Recent investigation supports this observation where total n-3 PUFAs of normozoospermic individual's semen were significantly higher than those from men with oligozoospermia, asthenozoospermia, and oligoasthenozoospermia [71]. In addition, in normozoospermic subjects, it was shown that about 50%, 30%, and 20% of the total FAs were composed of SFAs, PUFAs, and MUFAs, respectively.…”
Section: Fatty Acids In Human Spermatozoamentioning
confidence: 82%
“…Conclusively, data available so far on human and animal investigations suggest that supplementation of omega-3-fatty acids in male [27][28][29] as well female individuals [16,[19][20] improves reproductive success. Therefore, an omega-3-fatty acid supplementation as part of alimentary modification should be considered to improve female as well as male fertility in a multimodal approach.…”
Section: Resultsmentioning
confidence: 99%
“…Standardized alimentary supplementation of omega-3-fatty acids before and during an in vitro fertilization therapy so far has not been subject of a well-designed randomized prospective study. Just few small, prospective cohort studies have examined the relationship between serum omega-3-fatty acid levels and IVF-success with conflicting results [16][17][18][19][20]. One of the first approaches to study the correlation of omega-3-fatty acid supplementation and the probability of a pregnancy is the PREPARE-trial by Kermack and co-workers [15], which has not been finished yet.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported a high concentration of DHA in the spermatozoa of normozoospermic subjects [ 3 , 10 , 27 , 29 ]. Recently, it was observed that total n-3 PUFA of normozoospermic semen samples was significantly higher than those from oligozoospermic, asthenozoospermic, and oligoasthenozoospermic individuals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%